Acute changes in left atrial appendage function with premature ventricular complexes - Suresh Kumar Sukumaran; Anish Bhargav; Sridhar Balaguru; Avinash Anantharaj; Santhosh Satheesh; Raja J. Selvaraj (Indian Heart Journal)
Objectives: Left atrial appendage (LAA) dysfunction is a risk factor for stroke. Evidence shows that frequent premature ventricular complexes (PVCs) are associated with embolic stroke. Whether left atrial dysfunction is the bridging link between frequent premature ventricular complexes and stroke is unknown. Materials and methods: Patients with a structurally normal heart undergoing elective electrophysiology study were included. Transoesophageal echo was used to measure LAA flow velocities. To simulate PVCs in bigeminal rhythm, single paced beats were delivered from the right ventricle with a coupling interval of QT + 10 % RR interval after each sinus beat. LAA flow doppler velocities were acquired at baseline, after 5 min of pacing and again 5 min after cessation of pacing. Results: Ten patients were included in the study. Late diastolic emptying velocity decreased significantly after 5 min of PVCs (55.68 ± 16.33 cm/s, p = 0.01) compared to baseline (68.01 ± 10.34 cm/s). This almost returned to baseline after a rest period of 5 min (63.13 ± 16.16 cm/s, p = 0.277). The left atrial appendage filling velocity exhibited a statistically non-significant trend toward a decrease after 5 min of PVCs (45.70 ± 10.85 cm/s, p = 0.129), compared to the baseline value of 51.31 ± 14.11 cm/s. Conclusions: Premature ventricular complexes in bigeminal pattern for 5 min resulted in an acute decrease in the late diastolic emptying velocity. This is a possible mechanism for the increased risk of strokes in patients with frequent PVCs.